SISTEM INFORMASI ABSENSI MENGGUNAKAN ARDUINO BERBASIS SCANNER RFID DI SD NEGERI LANGENSARI 03 - Ardi Wicaksono, Dhito; Suhartono, Bambang; Setiawan, Dwi (Jurnal Ilmiah Sistem Informasi, 2023)
Attendance is a data collection activity to determine the number of people present at an event. Every activity always requires information about participant attendance. This also happens in the learning process. The benefit of attendance using an Arduino based RFID scanner is that it makes it easier for attendance officers to input practical data because they can retrieve and store attendance data from RFID tags directly. Research on the development of attendance to become more effective in the education sector. Every activity that requires information about participant attendance will definitely utilize the use of tools that are used as proof of participant attendance, while teacher attendance currently used is using fingerprints. When absent, problems often occur, namely the finger that will be used to do the fingerprinting. Based on the background above, the author created automatic attendance to make attendance easier while at the agency where the teacher teaches. Meanwhile, the barcode scanner is a faster data input process compared to the manual method. This input process can be done with a scanner to record the data contained in the barcode quickly, so it doesn't need to take a lot of time.